Performance evaluation of GlusterFS and NFS in Cloud Environment - أحمد, أحمد (Latakia University Journal -Engineering Sciences Series, 2024)
In distributed storage, data is transmitted and stored remotely on the Cloud Storage Systems where data can be backed up and maintained and made available for the users anywhere. Outside users only see the Distributed File System (DFS) as a single storage device. Nowadays, the Need of storing huge amounts of data has become a great challenge. A DFS provides many advantages over a local file system such as reliability, scalability, security… etc. Therefore, it was necessary to improve storage techniques to achieve the desired goals by relying on distributing data on clusters of servers with high specifications and loaded with high-performance systems. Although, there are a big set of distributed file systems, we have, in this paper, tested, from a performance point of view, two of the main known storage solution: GlusterFS, and NFS. As a distributed architecture, we studied their performance with different topologies and different transmitted data chunks, regarding: Read, Re-Read, Write, Re-Write Processes. Results showed that GlusterFS outperforms NFS, as NFS can only do a small subset of what GlusterFS offers.